Přístavba školy - Jirčík, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Obsahem diplomové práce je statický návrh nosných částí přístavby učebnicového pavilonu základní školy v Mirošově. Navrhovaný objekt je čtyřpodlažní železobetonová monolitická sloupová konstrukce. Stropy nad prvními třemi podlažími jsou řešeny jako křížem vyztužené desky s vnitřními průvlaky. Střešní deska je tvořena monolitickou deskou s dodatečně předpjatými trámy. Vnitřní síly byly vypočteny pomocí softwaru SCIA Engeneer 19.0, tyto hodnoty byly následně ověřeny ručním výpočtem. Při návrhu se postupovalo dle platných evropských norem. Výsledkem práce je statické posouzení objektu a odpovídající výkresová dokumentace.

The content of the thesis is a static design of the supporting parts of the extension of the textbook pavilion of the elementary school in Mirošov. The proposed building is a four-storey reinforced concrete monolithic column construction. The ceilings above the first three floors are designed as cross-reinforced slabs with internal girders. The roof slab consists of a monolithic slab with additionally prestressed beams. The internal forces were calculated using SCIA Engeneer 19.0 and these values were subsequently verified by manual calculation. The design followed the applicable European standards. The result of the work is a static assessment of the object and corresponding drawing documentation.
Extension of School
Keywords: Přístavba; základní škola; železobeton; předpjatý beton; betonářská výztuž; trámový strop; předpjatý trám; křížem vyztužená deska; průvlak; sloup; interakční diagram.; Extension; elementary school; reinforced concrete; prestressed concrete; concrete reinforcement; beam ceiling; prestressed beam; cross-reinforced slab; beam; column; interaction diagram.